The problem of characterising stationary data for the vacuum Einstein equations - Tod, P (IOP Publishing, 2017)
We take a step towards characterising stationary data for the vacuum Einstein equations, by finding a necessary condition on initial data for which the evolution is a solution of the vacuum equations admitting a Killing vector, which is time-like at least in some region of the Cauchy development.